Tanda WAQF dalam Al-Quran Al-Karim : analisis surah Al-Kahfi berdasarkan Rasm Uthmani / Ahmad Farid Fadhli Mustafa - Ahmad Farid Fadhli, Mustafa (2012)
This research is conducted in order to study and analyze the relationship between stops in reading in the Qur‟ān and signs in semantic knowledge. In this study, the author reveals the chronology of the publishing of the Qur‟ān by looking at the origin of it‟s writing through history. In this study, the author reviews places to stop reading the Qur‟ān by looking at it‟s use based in the views of the scholars, particularly in the field of Arabic, tajwid, history and others. Therefore the author uses the method of library research in this study, by extracting sentences containing stop signs of reading, in the Qur‟ān to be studied and analyzed. From the result of this study, the author found that there were 43 sentences that contained stop-signs from the Qur‟ān, out of 110 sentences in surah al-Kahf. The author also found that there were four stop-signs being used in reading the Qur‟ān. The overall result of the study, found that stop-signs used in reading the Qur‟ān had little to do with punctuation in common writing. It is seen that more attention was given to the continuation of the story without damaging the meaning in the sentence. Research like this is very important to be brought forward to the community so that they can understand the meaning of the Qur‟ān, exactly based on correct reading.